Origin and age of low-temperature carbonates in oceanic hotspot lavas - Ruixia Bai; Matthew G. Jackson; Yifan Du; Andrew Kylander-Clark; Andrea Giuliani; Senan Oesch; Adrian R. Tasistro-Hart; Benjamin Byerly; Gareth Seward; James M.D. Day; Elizabeth A. Bell (Geochimica et Cosmochimica Acta, 2026)

Embryo and Larval Developmental Staging Guides for Striped Bass - Erimi Kendrick; Nadya Mamoozadeh; William G. Cope; Russell Borski; Robert W. Clark; Michael S. Hopper; Benjamin J. Reading (Fishes, 2026)
Reliable developmental benchmarks are essential for synchronizing incubation and first-feeding decisions in striped bass (Morone saxatilis) hatcheries, yet existing references are incomplete, outdated, or difficult to apply across variable temperature regimes. We developed contemporary embryo and larval developmental staging guides for striped bass using digital imaging and degree day standardization and paired these guides with measurements of early larval mortality and endogenous energy depletion to provide practical context for hatchery management. Larvae were photographed from hatch through metamorphosis to document key morphological transitions, including yolk absorption, mouth formation, swim bladder inflation, fin differentiation, pigmentation, and diet-related developmental milestones. To place these stages in physiological and survival context, aquarium trials showed there was no clear density-dependent mortality across rearing densities of 1.1–6.8 larvae/mL within the first 72 h post-hatch. Yolk reserves were typically depleted by approximately 4–6 days post-hatch (dph), while lipid droplets persisted longer as secondary endogenous energy stores in unfed larvae through 15 dph. Together, these staging guides provide a transferable developmental framework from fertilization to metamorphosis that links external morphology to endogenous reserve depletion and first feeding, thus supporting standardized hatchery monitoring, improved feeding synchronization, and more consistent assessment of embryo and larval quality.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Discovery of young submarine volcanism in the Cook Islands: New constraints on the location of the Rarotonga hotspot - Yifan Du; Matthew G. Jackson; Brian Jicha; Andrew Kylander-Clark; Benjamin L. Byerly; Michael Bizimis; Sæmundur Ari Halldórsson; Gareth G.E. Seward; Olivia E. Anderson; Matthew Rioux; Kevin Konrad; Sunna Harðardóttir; et al. (Geochimica et Cosmochimica Acta, 2026)

Clumped isotope constraints on secondary mineral formation and thermal overprinting in the Michigan Basin, Southwestern Ontario - Benjamin R. Fosu; Josué J. Jautzy; Duane C. Petts; Ian D. Clark; Tom A. Al (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Genomic Analysis of Hair Sheep From West/Central Africa Reveals Unique Genetic Diversity and Ancestral Links to Breed Formation in the Caribbean - Pamela Wiener; Juliane Friedrich; Melissa M. Marr; Gustave Simo; Vincent N. Tanya; Keith T. Ballingall; Pavel Flegontov; Benjamin D. Rosen; Guillaume Sallé; Gordon Spangler; Curtis P. Van Tassell; Mazdak Salavati; et al. (Molecular Ecology, 2025)
Cameroon Blackbelly sheep are a domestic breed of hair sheep from West/Central Africa. They are popular with small‐holder farmers in Cameroon as they are highly resilient to local environmental challenges and are prolific a‐seasonal breeders. The aim of this study was to characterise the genetics of Cameroon Blackbelly sheep in relation to global sheep populations and to investigate their relationship to Caribbean hair sheep. We first examined the genetic diversity of the Cameroon Blackbelly breed relative to global sheep populations using 50K SNP data. We also used whole genome sequence data to further investigate relationships between Cameroon Blackbelly and breeds from Africa and Europe, as well as the Barbados Blackbelly breed from the Caribbean, which is phenotypically similar to Cameroon Blackbelly. ADMIXTURE results based on 50K and WGS data demonstrated both West/Central African and European ancestries for the Barbados Blackbelly sheep. Results from f 4 ‐statistics‐based qpAdm analyses supported these findings. Local ancestry inference identified several genomic regions in Barbados Blackbelly with high proportions of West/Central African ancestry. One of these, on OAR3, includes various keratin genes, suggesting that these genes may play a role in the shared coat phenotypes of the Barbados Blackbelly and Cameroon Blackbelly. This result is consistent with previous reports of adaptive introgression of coat characteristics in both wild and domesticated species. The findings of our study support the view that sheep were transported from West/Central Africa to the Caribbean as part of the transatlantic slave trade and European colonisation, similar to introductions proposed for cattle and goats.

Regional differentiation in somatic growth and maturation attributes for loggerhead sea turtles (Caretta caretta) in the Northwest Atlantic - Larisa Avens; Margaret M. Lamont; Allen M. Foley; Benjamin M. Higgins; Lyndsey N. Howell; Gretchen Lovewell; Donna J. Shaver; Brian A. Stacy; J. Shelby Walker; Jamie M. Clark; Amy A. Wallace; Hannah B. Vander Zanden (Marine Biology, 2025)

Adsorption of MC-LR enabled by customizable 3D printed graphene-coated structures - Justin D. Puhnaty; Jacob M. Lalley; Alan J. Kennedy; Jaylen A. Davis; Angela M. Evans; Sarah Grace Zetterholm; Connor C. Clark; Jesse L. Roberts; Christopher S. Griggs; Benjamin S. Magbanua (Journal of Environmental Chemical Engineering, 2025)

Influence of four hook types across four hook removal tools, including bare hands, on the effectiveness of hook removal and reflex impairment of Bluegill ( Lepomis macrochirus ) captured from a lake in Eastern Ontario - Jeremy Hussey; Luc LaRochelle; Andy J. Danylchuk; Sascha Clark Danylchuk; Benjamin W. C. Cooke; Joshua T. H. Cooke; Cameron J. A. Cooke; Steven J. Cooke (Fisheries Management and Ecology, 2025)
Hook removal devices have been developed to enable rapid release of angled fish, yet little research has evaluated their effectiveness and potential for injury among hook types. We compared the performance of hook removal tools and bare hands with four hook types on freshwater Lepomid sunfish. Dehooking performance was assessed using hook removal time, unhooking difficulty, degree of tissue damage at the hooking location, and immediate reflex impairment. Unhooking difficulty was positively related to hooking depth. Unhooking difficulty was lowest for hemostats and the mechanical dehooking device; however, the mechanical dehooking device caused the largest tearing of mouth tissue. Unhooking difficulty was the main driver for hook removal time, tissue tear length, and overall reflex impairment. Hooks that were harder to remove caused higher reflex impairment. Hook type had little influence on the effectiveness of hook removal tools, although circle hooks were more difficult to remove and caused greater injury when using tools. Although use of hook removal tools can be beneficial for fish that are released, more research is needed on more species targeted by recreational anglers, and more hook removal tools. We suggest that hemostats should be used to remove hooks from fish to reduce unhooking difficulty, tissue tears, long air exposure, and thereby to increase the welfare of the fish.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Inequities blocking the path to circular economies: A bio-inspired network-based approach for assessing the sustainability of the global trade of waste metals - Filippos K. Zisopoulos; Brian D. Fath; Susana Toboso-Chavero; Hao Huang; Daan Schraven; Benjamin Steuer; Alexandros Stefanakis; O.Grant Clark; Serban Scrieciu; Simron Singh; Dominik Noll; Martin de Jong (Resources, Conservation and Recycling, 2025)

Vitifolignans, 3,4-dibenzyltetrahydrofuran lignans from Anemone vitifolia Buch.-Ham - Ya Lu; Xueyan Huang; Donovon A. Adpressa; Linyun Mou; Peter R. Taylor; Benjamin R. Clark (Phytochemistry, 2024)

Secondary metabolites from Penicillium chrysogenum WX6 and their chemotaxonomic significance - Ya Lu; Jessica Villegas-Moreno; Benjamin R. Clark (Biochemical Systematics and Ecology, 2024)

Mining exploration infrastructure affects biophysical habitat characteristics and ground-dwelling arthropod communities - Kristen Fernandes; Sophia Clark-Ioannou; Benjamin J. Saunders; Jonathan Majer; Philip W. Bateman; Michael Bunce; Paul Nevill (Biodiversity and Conservation, 2024)
Monitoring of environmental impacts of mining activities typically focuses on the main operation footprint, neglecting exploration infrastructure like tracks, roads, and drill pads. These areas are cleared of native vegetation and impacts on the surrounding environment can be both cumulative and enigmatic. Here, we study the impacts of mining exploration infrastructure on habitat characteristics and ground-dwelling arthropod communities in the Midwest region of Western Australia. The study was conducted at three mine sites, each with three infrastructure types: maintained tracks, unmaintained tracks, and drill pads along transects extending 100 m away from the disturbance into remnant vegetation. Habitat characteristics were measured, and arthropods collected from pitfall traps along these transects and identified using COI metabarcoding. The overall arthropod community and two indicator groups, ants (Formicidae) and springtails (Collembola) - were used to measure arthropod responses to changes in response to habitat disturbance. Whilst changes in habitat were only visible to 10 m from the disturbance, impacts on arthropod communities could be detected up to 100 m into the remnant vegetation, and these responses were more complex. In general, we found similar patterns expressed in the compositional changes for arthropods overall and between our chosen indicator groups, but they were not the same across all sites and infrastructure types. Our results demonstrate the utility of bulk arthropod metabarcoding and different arthropod indicator groups for documenting the effects of fine-scale habitat destruction, degradation, or disturbance. They also highlight the need to monitor the negative impacts of mineral exploration on the environment.

Taylor’s law for exponentially growing local populations linked by migration - Samuel Carpenter; Scout Callens; Clark Brown; Joel E. Cohen; Benjamin Z. Webb (Theoretical Population Biology, 2023)

Status of intertidal populations of Pismo clams (Tivela stultorum) across their range in California - Alexandria R. Marquardt; Sara K. Park; Eliana G. Maietta; Noël M. Clark; Grant T. Waltz; Lisa A. Needles; Benjamin I. Ruttenberg (Regional Studies in Marine Science, 2023)

Landscape Connectivity For Wildlife and Water: The State of the Literature - Ruth DeFries; Satvik Parashar; Amrita Neelakantan; Benjamin Clark; Jagdish Krishnaswamy (Current Landscape Ecology Reports, 2023)
Purpose of Review The science of landscape connectivity is widely applied to identify corridors for wildlife movement through unprotected areas. Where corridors coincide with forested or vegetated headwater catchments, they can contribute to blue water security for downstream users and recycle precipitation through green water flux to the larger region. This review examines the extent to which hydrology is recognized within studies on wildlife corridors. We illustrate the synergy between wildlife corridors and water security in the Central Indian Highlands, a globally important region for tiger ( Panthera tigris ) conservation and the water tower for five major rivers. Recent Findings We find that a growing but still minor component of the literature on landscape connectivity addresses hydrology. Out of 127 publications on landscape connectivity that address both hydrology and wildlife, 50% were published after 2015 and hydrology-related words appear more frequently in abstracts over time (27% in 1993–2003 and 45% in 2014–2023 of most frequently used words) The case study illustrates potential synergies for water security and conservation, with areas for wildlife connectivity twice as rugged, three times more forested, and about 1.8 times denser with small streams than other areas in the landscape. About half of the area identified for landscape connectivity overlaps with catchment areas for five major dams. Summary Freshwater resources and water security are vital in human-dominated landscapes such as central India. A holistic view of landscape connectivity beyond wildlife provides practitioners with additional rationale for conserving these areas to maintain water resources that are directly relevant to people living in the landscape.

The effect of mobility-related anxiety on walking across the lifespan: a virtual reality simulation study - Tiphanie E. Raffegeau; Mindie Clark; Bradley Fawver; Benjamin T. Engel; William R. Young; A. Mark Williams; Keith R. Lohse; Peter C. Fino (Experimental Brain Research, 2023)

Stream fish community structure across an urban gradient in a northeastern US watershed - Daniel P. Welsh; John P. Ludlam; Emma L. Downs; Elizabeth S. Gordon; Elyse V. Clark; Benjamin Levy; Jane Huang; Aisling M. O’Connor (Environmental Biology of Fishes, 2023)

Geographical contrasts of Y‐chromosomal haplogroups from wild and domestic goats reveal ancient migrations and recent introgressions - Isaäc J. Nijman; Benjamin D. Rosen; Philippe Bardou; Thomas Faraut; Tristan Cumer; Kevin G. Daly; Zhuqing Zheng; Yudong Cai; Hojjat Asadollahpour; Bengi Çınar Kul; Wei‐Yi Zhang; Guangxin E.; et al. (Molecular Ecology, 2022)
By their paternal transmission, Y‐chromosomal haplotypes are sensitive markers of population history and male‐mediated introgression. Previous studies identified biallelic single‐nucleotide variants in the SRY , ZFY and DDX3Y genes, which in domestic goats identified four major Y‐chromosomal haplotypes, Y1A, Y1B, Y2A and Y2B, with a marked geographical partitioning. Here, we extracted goat Y‐chromosomal variants from whole‐genome sequences of 386 domestic goats (75 breeds) and seven wild goat species, which were generated by the VarGoats goat genome project. Phylogenetic analyses indicated domestic haplogroups corresponding to Y1B, Y2A and Y2B, respectively, whereas Y1A is split into Y1AA and Y1AB. All five haplogroups were detected in 26 ancient DNA samples from southeast Europe or Asia. Haplotypes from present‐day bezoars are not shared with domestic goats and are attached to deep nodes of the trees and networks. Haplogroup distributions for 186 domestic breeds indicate ancient paternal population bottlenecks and expansions during migrations into northern Europe, eastern and southern Asia, and Africa south of the Sahara. In addition, sharing of haplogroups indicates male‐mediated introgressions, most notably an early gene flow from Asian goats into Madagascar and the crossbreeding that in the 19th century resulted in the popular Boer and Anglo‐Nubian breeds. More recent introgressions are those from European goats into the native Korean goat population and from Boer goat into Uganda, Kenya, Tanzania, Malawi and Zimbabwe. This study illustrates the power of the Y‐chromosomal variants for reconstructing the history of domestic species with a wide geographical range.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Tri‐trophic interactions mediate the spread of a vector‐borne plant pathogen - Robert E. Clark; Saumik Basu; Benjamin W. Lee; David W. Crowder (Ecology, 2019)
Many insect herbivores are vectors that transmit plant pathogens as they forage. Within food webs, vectors interact with a range of host plants, other herbivores, and predators. Yet, few studies have examined how tri‐trophic interactions involving vectors affect the spread of pathogens. Here we assessed effects of food web structure on aphid vectors and the prevalence of an aphid‐borne persistent pathogen (Pea enation mosaic virus, PEMV ) in pea plants. We experimentally manipulated ladybird predators, alternative host plants, and non‐vector herbivores and assessed responses of pea aphids and PEMV using structural equation models. We show that variation in bottom‐up, top‐down, and horizontal interactions mediated PEMV prevalence. Predators reduced PEMV prevalence by consuming aphids, but an alternative host plant (vetch) had the opposite effect by promoting aphid movement and abundance. Non‐vector herbivores (pea leaf weevil) increased PEMV susceptibility in peas. In turn, weevils offset the positive effects of predators on PEMV , but increased the negative effects of vetch. Our results show that tri‐trophic interactions within insect and plant food webs can mediate vector biology with synergistic and opposing effects on pathogens. Continuing to assess how community‐wide interactions affect vectors will aid in our understanding of vector‐borne pathosystems.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

DNA barcoding of traded shark fins, meat and mobulid gill plates in Singapore uncovers numerous threatened species - Benjamin J. Wainwright; Yin Cheong Aden Ip; Mei Lin Neo; Jia Jin Marc Chang; Chester Zhikai Gan; Naomi Clark-Shen; Danwei Huang; Madhu Rao (Conservation Genetics, 2018)

Cardiogoniometry Compared to Fractional Flow Reserve at Identifying Physiologically Significant Coronary Stenosis: The CARDIOFLOW Study - Oliver I. Brown; Andrew L. Clark; Raj Chelliah; Benjamin J. Davison; Adam N. Mather; Michael S. Cunnington; Joseph John; Albert Alahmar; Richard Oliver; Konstantinos Aznaouridis; Angela Hoye (Cardiovascular Engineering and Technology, 2018)

Chemical and genetic differences between Hawaiian lineages of the alga Asparagopsis taxiformis - Benjamin R. Clark; Mindy Mizobe; Jerry L. M. Kaluhiwa; Jo-Ann Leong; Robert P. Borris (Journal of Applied Phycology, 2018)

Trace element mapping by LA-ICP-MS: assessing geochemical mobility in garnet - Tom Raimondo; Justin Payne; Benjamin Wade; Pierre Lanari; Chris Clark; Martin Hand (Contributions to Mineralogy and Petrology, 2017)

Intra-annual dynamics of water stress in the central Indian Highlands from 2002 to 2012 - Benjamin Clark; Ruth DeFries; Jagdish Krishnaswamy (Regional Environmental Change, 2016)

Dissolution Testing for Bioavailability of Over-the-Counter (OTC) Drugs—a Technical Note - Zongming Gao; Lawrence Yu; Stephanie Clark; Mike Trehy; Terry Moore; Benjamin Westenberger; Lucinda Buhse; John Kauffman; Benjamin Bishop; Lydia Velazquez; Scott Furness (AAPS PharmSciTech, 2015)

Comparison Between Bench-Top and Computational Modelling of Cerebral Thromboembolism in Ventricular Assist Device Circulation - William D. Clark; Benjamin A. Eslahpazir; I. Ricardo Argueta-Morales; Alain J. Kassab; Eduardo A. Divo; William M. DeCampli (Cardiovascular Engineering and Technology, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Leaf physiology and morphology of Castanea dentata (Marsh.) Borkh., Castanea mollissima Blume, and three backcross breeding generations planted in the southern Appalachians, USA - Benjamin O. Knapp; G. Geoff Wang; Stacy L. Clark; Lauren S. Pile; Scott E. Schlarbaum (New Forests, 2014)

Colour discrimination and associative learning in hatchling lizards incubated at ‘hot’ and ‘cold’ temperatures - Benjamin F. Clark; Joshua J. Amiel; Richard Shine; Daniel W. A. Noble; Martin J. Whiting (Behavioral Ecology and Sociobiology, 2014)

Experimental manipulation of seed shadows of an Afrotropical tree determines drivers of recruitment - John R. Poulsen; Connie J. Clark; Benjamin M. Bolker (Ecology, 2012)
The loss of animals in tropical forests may alter seed dispersal patterns and reduce seedling recruitment of tree species, but direct experimental evidence is scarce. We manipulated dispersal patterns of Manilkara mabokeensis , a monkey‐dispersed tree, to assess the extent to which spatial distributions of seeds drive seedling recruitment. Based on the natural seed shadow, we created seed distributions with seeds deposited under the canopy (“no dispersal”), with declining density from the tree (“natural dispersal”), and at uniform densities (“good dispersal”). These distributions mimicked dispersal patterns that could occur with the extirpation of monkeys, low levels of hunting, and high rates of seed dispersal. We monitored seedling emergence and survival for 18 months and recorded the number of leaves and damage to leaves. “Good dispersal” increased seedling survival by 26%, and “no dispersal” decreased survival by 78%, relative to “natural dispersal.” Using a mixed‐effects survival model, we decoupled the distance and density components of the seed shadow: seedling survival depended on the seed density, but not on the distance from the tree. Although community seedling diversity tended to decrease with longer dispersal distances, we found no conclusive evidence that patterns of seed dispersal influence the diversity of the seedling community. Local seed dispersal does affect seedling recruitment and survival, with better dispersal resulting in higher seedling recruitment; hence the loss of dispersal services that comes with the reduction or extirpation of seed dispersers will decrease regeneration of some tree species.

Biodegradation of polyfluorinated biphenyl in bacteria - David Hughes; Benjamin R. Clark; Cormac D. Murphy (Biodegradation, 2011)

GEOCHEM-EZ: a chemical speciation program with greater power and flexibility - Jon E. Shaff; Benjamin A. Schultz; Eric J. Craft; Randy T. Clark; Leon V. Kochian (Plant and Soil, 2010)

Understanding movement data and movement processes: current and emerging directions - Robert S. Schick; Scott R. Loarie; Fernando Colchero; Benjamin D. Best; Andre Boustany; Dalia A. Conde; Patrick N. Halpin; Lucas N. Joppa; Catherine M. McClellan; James S. Clark (Ecology Letters, 2008)
Animal movement has been the focus on much theoretical and empirical work in ecology over the last 25 years. By studying the causes and consequences of individual movement, ecologists have gained greater insight into the behavior of individuals and the spatial dynamics of populations at increasingly higher levels of organization. In particular, ecologists have focused on the interaction between individuals and their environment in an effort to understand future impacts from habitat loss and climate change. Tools to examine this interaction have included: fractal analysis, first passage time, Lévy flights, multi‐behavioral analysis, hidden markov models, and state‐space models. Concurrent with the development of movement models has been an increase in the sophistication and availability of hierarchical bayesian models. In this review we bring these two threads together by using hierarchical structures as a framework for reviewing individual models. We synthesize emerging themes in movement ecology, and propose a new hierarchical model for animal movement that builds on these emerging themes. This model moves away from traditional random walks, and instead focuses inference on how moving animals with complex behavior interact with their landscape and make choices about its suitability.

First Record of Stygimys (Mammalia, Multituberculata, Eucosmodontidae) from the Paleocene (Puercan) Part of the North Horn Formation, Utah, and a Review of the Genus - Donald L. Lofgren; Benjamin E. Scherer; Charles K. Clark; Barbara Standhardt (Journal of Mammalian Evolution, 2005)

Regeneration in Gap Models: Priority Issues for Studying Forest Responses to Climate Change - David T. Price; Niklaus E. Zimmermann; Peter J. van der Meer; Manfred J. Lexer; Paul Leadley; Irma T. M. Jorritsma; Jörg Schaber; Donald F. Clark; Petra Lasch; Steve McNulty; Jianguo Wu; Benjamin Smith (Climatic Change, 2001)